Characteristics of the type 2 diabetic patients with hypoglycemia in a tertiary referral hospital - Satilmis Bilgin (Publishing House Zaslavsky, 2021)
Background. Hypoglycemia is an important complication of the treatment of type 2 diabetes mellitus, which constitutes a barrier in stringent diabetic control. Beside it constitutes nearly 10 % of emergency department admissions that caused by adverse drug events, it may also increase morbidities and mortality by inducing, cardiac arrhythmias, neurological impairment and ischemic events. Hypoglycemia is the most common side effect of insulin treatment, however, oral antidiabetic agents may also induce hypoglycemic complications. In present retrospective study, we purposed to observe general characteristics and laboratory data of the type 2 diabetic patients whom presented with mild or moderate/severe hypoglycemia. Materials and methods. Patients with type 2 diabetes mellitus whom presented to our institution with hypoglycemia between January 2019 and January 2020 were retrospectively analyzed. General characteristics and laboratory data of the subjects recorded. Patients grouped into two groups, group I consisted of subjects with mild hypoglycemia and group II consisted of patients with moderate/severe hypoglycemia. Data of the subjects in groups I and II were compared. Results. There were 15 subjects in group I and 23 in group II. HbA1c and other laboratory markers were not significantly different in study groups. Similarly diabetes duration and anti-diabetic treatment were not significantly different in study groups. The rate of geriatric patients was significantly higher in group II compared to group I (p = 0.04). Conclusions. Subjects with moderate/severe hypoglycemia tend to be more frequently in geriatric age and HbA1c not correlates with the degree of the hypoglycemia. Since neither duration of diabetes, nor anti-diabetic treatment were associated with the severity of the hypoglycemia, each case should be evaluated individually to prevent further episodes which could increase morbidity and mortality in diabetic population.